Mulheres e forças armadas: uma análise da participação feminina nas Forças Armadas Brasileiras. - Dantas, Stela da Rocha de Medeiros (2018)
The present study aims to analyze the participation of women in the Brazilian Armed Forces. The study of this phenomenon becomes relevant in the field of politics, since following socially established patterns, women are excluded from important public life issues and, since the Armed Forces is based on androcentrism, it tends to prioritize masculine attributes to the detriment of women, women who choose to pursue this career end up facing challenges that limit them inside the barracks. These visions are shared, for example, in the academy of International Relations, since areas such as International Security and Defense tend to be exclusive to women, since they are areas considered masculine. Thus, the work is relevant, since it seeks to portray the way women participate and act in means traditionally excluding their presence, thus showing that stereotypes still guide the main debates and functions in the social scene. In view of this, the problem question that the work seeks to answer how does the way women's participation in the Brazilian Armed Forces. The methodology used was the case study and, through a qualitative study, the work was the result of a bibliographical review, in which texts and relevant authors of the subject were selected, as well as official documents from Brazil. The results obtained assume that the female participation in environments considered as masculine faces obstacles and end up bumping into socially constructed myths and discourses.